2020
DOI: 10.1371/journal.pone.0236870
|View full text |Cite
|
Sign up to set email alerts
|

Child-oriented and partner-oriented perfectionism explain different aspects of family difficulties

Abstract: The aim of the study was to verify the relationship between child-oriented and partner-oriented perfectionism, and their associations with narcissism and with difficulties in the romantic and parental domains. A total of 459 individuals participated, 264 women and 195 men (Mage = 33.88, SD = 4.39). Child-oriented perfectionism and partner-oriented perfectionism were related to each other and positively correlated with narcissism. Partner-oriented perfectionism turned out to be a specific predictor of difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…The data collected and analyses conducted show that the Polish version of the BTPS adequately captures the conceptualization of perfectionism proposed by Smith, Saklofske, Stoeber, and colleagues (2016). Another goal of the conducted studies was to verify the utility of the Polish-language version of the BTPS by observing the relationship of the three dimensions with other perfectionism scales, which measured aspects of personal standards perfectionism, evaluative concerns (Frost et al, 1990), and child-oriented perfectionism (Piotrowski, 2020). Second, we analyzed the relationships between the BTPS dimensions and indicators of psychological and emotional difficulties: borderline symptoms, parental stress, and parental burnout (Piotrowski, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The data collected and analyses conducted show that the Polish version of the BTPS adequately captures the conceptualization of perfectionism proposed by Smith, Saklofske, Stoeber, and colleagues (2016). Another goal of the conducted studies was to verify the utility of the Polish-language version of the BTPS by observing the relationship of the three dimensions with other perfectionism scales, which measured aspects of personal standards perfectionism, evaluative concerns (Frost et al, 1990), and child-oriented perfectionism (Piotrowski, 2020). Second, we analyzed the relationships between the BTPS dimensions and indicators of psychological and emotional difficulties: borderline symptoms, parental stress, and parental burnout (Piotrowski, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other-oriented perfectionism, studies to date have confirmed their disruptive effects on child development and the parent himself (Smith et al, 2017), but a limitation of these studies has been defining this characteristic as a general, non-specific tendency. However, recent studies have confirmed that the expectation of perfection differs for different family members (Piotrowski, 2020), justifying studies focused on specific interpersonal relationships. In the parenthood context, studies on child-oriented perfectionism appear to be particularly relevant, but they are extremely rare (Lin et al, 2022; Piotrowski, 2020), making it still unclear what the relationship between child-oriented perfectionism and other aspects of perfectionism is.…”
Section: Perfectionism and Parentingmentioning
confidence: 99%
See 3 more Smart Citations